2004
DOI: 10.1007/s00586-004-0720-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic response of lumbar functional spinal units to axial torsion with and without superimposed compression and flexion/extension

Abstract: Experimental data suggest that lumbar torsion contributes to lumbar disc degenerative changes, such as instability, spondylolisthesis and spinal canal stenosis. However, some basic mechanical characteristics of the lumbar spine under torsional loading have not yet been reported in detail. For example, the function of the facet joints under combined mechanical loads such as torsion with superimposed flexion or extension postures is an area of interest about which little biomechanical data have been reported. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 41 publications
2
30
0
13
Order By: Relevance
“…This may have been due to anatomical differences between the two species. In humans, pure axial rotation ceases when the sagittally-oriented facet joints come into contact [28], while the kinematics of lumbar joint segments have not been studied extensively in cats. Lumbar facets in cats have slightly different orientations, with the superior and inferior facets facing medial-posteriorly and lateralanteriorly, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to anatomical differences between the two species. In humans, pure axial rotation ceases when the sagittally-oriented facet joints come into contact [28], while the kinematics of lumbar joint segments have not been studied extensively in cats. Lumbar facets in cats have slightly different orientations, with the superior and inferior facets facing medial-posteriorly and lateralanteriorly, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…But for reasons of physics, such data did not give any indication for segment kinematics. One held a priori that the spinal kinematics would be geometrically simple since the ROM amounted to only few degrees: The upper segment would rotate in relation to the lower around a segmentally fixed rotational axis (Panjabi et al, 1981; or would helically move around a fixed helical axis of motion, the HAM (Zhu et al, 2007;Haberl et al, 2004;Niosi et al, 2006). The position of HAM was calculated from two measured positions of the moved vertebra, which differed nearly by ROM.…”
Section: Issue Of the Measuring Methodsmentioning
confidence: 99%
“…Chosa et al (2004) found that unilateral pars interarticularis stress was greatest under combinations of compression with lumbar extension, compression with lumbar side-flexion to the same side, and compression with lumbar rotation to the opposite side. Further, it is known that the available ROM of lumbar axial rotation is reduced when the spine is in end range extension (Haberl et al, 2004, Burnett et al, 2006, therefore implying increased stiffening of the spine when it is positioned near the limits of its physiological ROM. Panjabi (1992) terms this zone of high stiffness towards end range the "elastic zone of motion".…”
Section: Introductionmentioning
confidence: 99%